Загреб у фольклорі та літературі - Маркс, Л. (Народна творчість та етнологія, 2011)
For modern authors who often refer to traditional beliefs, Zagreb is depicted in differentuays – as a sentimental, autobiographic trip through the city; Zagreb’s legends are had in mind of the author from their childhood about the collision of Capitol and Grych, about the origin of the name of the Bloody bridge, about Mandushevec, about executing of Matia Gubac, about Divine Mother Lithoidal, saved from a fire, about the Black queen. The modern ideas about a city have a symbolic character: a city comes forward as a symbol of mother that protects, takes care of the children, the bright and warm feelings are related with it. Zagreb is always an open book for thousands of people, it contains many important and valuable stories. U suvremenih se autora koji prizivaju zagrebačku usmenu (ili povijesnu) tradiciju, Zagreb doživljuje dvojako – kao sentimentalno, autobiografsko, prustovsko putovanje gradom u kojemu se spominju i zagrebačke predaje kojih se autor prisjeća iz djetinjstva: o sukobu Kaptola i Griča i postanku imena Krvavi most, o Popovu tornju, o Manduševcu, o užarenu prijestolju Matije Gupca, o Majci Božjoj Kamenitoj spašenoj iz vatre, o Crnoj kraljici. I suvremenije su predodžbe o gradu naglašeno simbolične: grad je simbol majke koja zaštićuje iograničuje, koja nosi i čuva svoju djecu i priziva tople, afektivne predodžbe. Zagreb je vazda otvorena knjiga tisućama jedankovrijednih i razvnopravnih priča.